The Comparative Analysis of Mathematical Achievement, Self-Efficacy, and Self-Concept Based on the Perceived Classroom Climate Among Male and Female Students - Sheida Sharifi Saki; Mohammad Hossein Fallah; Hassan Zareei Mahmoodabadi; Reza Karimi (Shiraz University of Medical Sciences, 2014)
Background: Mathematics is one of the essential and effective subjects that dominate students' educational performance and occupational future. Objectives: The current study aimed to comparatively analyze the mathematical achievement, self-efficacy, and self-concept based on the perceived classroom climate among the male and female students. Patients and Methods: The study included 400 students (222 males and 178 females) as respondents from the third grade high school selected by cluster sampling technique considering educational regions, high schools, classrooms, and students. The participants answered the questions derived from three questionnaires, the so called WIHIC, mathematical self-efficacy, and mathematical self-concept description. Results: The results of route analysis indicated that mathematical self-efficacy rate was 8% and 7% among male and female students, respectively. The variance of mathematical self-concept based on the expressed perceived classroom climate was higher in female than male students (32% versus 26%). However, based on the internal variables in this model, the mathematics score was found to be higher among male than in female pupils (27% versus 13%). Conclusions: The findings of the route analysis showed that these differences are adjustable by variables such as mathematical self-efficacy.